Integrated Two‐Analyte Population Pharmacokinetic Model for Antibody–Drug Conjugates in Patients: Implications for Reducing Pharmacokinetic Sampling. (10th November 2016) - Lu, D; Gibiansky, L; Agarwal, P; Dere, RC; Li, C; Chu, Y‐W; Hirata, J; Joshi, A; Jin, JY; Girish, S
Abstract : An integrated pharmacokinetics (PK) model that simultaneously describes concentrations of total antibody (Tab) and antibody‐conjugated monomethyl auristatin E (acMMAE) following administration of monomethyl auristatin E (MMAE)‐containing antibody–drug conjugates (ADCs) was developed based on phase I PK data with extensive sampling for two ADCs. Two linear two‐compartment models that shared all parameters were used to describe the PK of Tab and acMMAE, except that the deconjugation rate was an additional clearance pathway included in the acMMAE PK model compared to Tab. Further, the model demonstrated its ability to predict Tab concentrations and PK parameters based on observed acMMAE PK and various reduced or eliminated Tab PK sampling schemes of phase II data. Thus, this integrated model allows for the reduction of Tab PK sampling in late‐phase clinical development without compromising Tab PK characterization.